Diagnosing sarcopenia: Functional perspectives and a new algorithm from the ISarcoPRM - Murat Kara; Bayram Kaymak; Walter Frontera; Ayşe Merve Ata; Vincenzo Ricci; Timur Ekiz; Ke-Vin Chang; Der-Sheng Han; Xanthi Michail; Michael Quittan; Jae-Young Lim; Jonathan F. Bean; et al. (Medical Journals Sweden, 2021)
Sarcopenia is an important public health problem, characterized by age-related loss of muscle mass and muscle function. It is a precursor of physical frailty, mobility limitation, and premature death. Muscle loss is mainly due to the loss of type II muscle fibres, and progressive loss of motor neurones is thought to be the primary underlying factor. Anterior thigh muscles undergo atrophy earlier, and the loss of anterior thigh muscle function may therefore be an antecedent finding. The aim of this review is to provide an in-depth (and holistic) neuromusculoskeletal approach to sarcopenia. In addition, under the umbrella of the International Society of Physical and Rehabilitation Medicine (ISPRM), a novel diagnostic algorithm is proposed, developed with the consensus of experts in the special interest group on sarcopenia (ISarcoPRM). The advantages of this algorithm over the others are: special caution concerning disorders related to the renin-angiotensin system at the case finding stage; emphasis on anterior thigh muscle mass and function loss; incorporation of ultrasound for the first time to measure the anterior thigh muscle; and addition of a chair stand test as a power/performance test to assess anterior thigh muscle function. Refining and testing the algorithm remains a priority for future research.